2012
DOI: 10.1136/bjophthalmol-2012-302469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic features in Italian Bietti crystalline dystrophy patients

Abstract: AimThe aim of the study was to describe the clinical and genetic features of 15 Italian patients with Bietti crystalline dystrophy (BCD).MethodsAll study participants underwent a complete ophthalmological examination, including standard electroretinogram (ERG), optical coherence tomography, microperimetry, autofluorescence and multifocal electroretinogram. The 11 exons of the CYP4V2 gene were sequenced. The effect of mutations on protein function was estimated by a combination of web based programs.Results15 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 24 publications
5
50
0
Order By: Relevance
“…Only rarely were crystals observed within the inner retina or deeper to the apical RPE and when this occurred it was typically in regions with severe RPE abnormalities, suggesting displacement. 21, 33, 34, 39-42 There was loss of the photoreceptor outer segment-RPE interface signal on SD-OCT across large expanses of the central retina even in the absence of crystals and in regions where a deceivingly normal ONL co-localized with abnormal vision. This relative dissociation between the abnormalities at the photoreceptor outer segment-RPE layer in the setting of a preserved ONL lends supports to the hypothesis that these are the structures primarily affected by the molecular defect.…”
Section: Discussionmentioning
confidence: 98%
“…Only rarely were crystals observed within the inner retina or deeper to the apical RPE and when this occurred it was typically in regions with severe RPE abnormalities, suggesting displacement. 21, 33, 34, 39-42 There was loss of the photoreceptor outer segment-RPE interface signal on SD-OCT across large expanses of the central retina even in the absence of crystals and in regions where a deceivingly normal ONL co-localized with abnormal vision. This relative dissociation between the abnormalities at the photoreceptor outer segment-RPE layer in the setting of a preserved ONL lends supports to the hypothesis that these are the structures primarily affected by the molecular defect.…”
Section: Discussionmentioning
confidence: 98%
“…49,55 Interestingly, clinical symptoms of BCD remain only in the eyes. The link between altered 32 Yin et al, 36 Meng et al, 59 Manzouri et al, 64 Shan et al 60 15 3 c.332T>C p.I111T Missense Li et al, 55 Astuti et al, 63 Rossi et al, 61 García-García et al, 65 Haddad et al, 66 Rossi et al 67 10 Lin et al, 11 Li et al, 17 Gocho et al, 27 Halford et al, 32 Yin et al, 36 Li et al, 55 Xiao et al, 57 Meng et al, 59 Astuti et al, 63 Nakamura et al, 68 Lee et al, 69 Chung et al, 70 Gekka et al, 71 Jin et al, 72 Liu et al, 73 Shan et al, 60 Tian et al, 62 Wada et al, 74 10 Li et al, 17 Li et al, 55 Xiao et al, 57 Meng et al, 59 36 Meng et al, 59 Mamatha et al 77 43 9 c.1091-2A>G Exon9del Splice site Li et al, 17 Yin et al, 36 Li et al, 55 Xiao et al, 57 Meng et al, 59 Shan et a...…”
Section: Role Of Cyp4v2 In Fatty Acid Metabolismmentioning
confidence: 98%
“…10,32,36,61,63,69 Our group has previously evaluated the genotype-phenotype correlation in a group of 18 Chinese patients in 13 families and showed that BCD with homozygous IVS6-8del17bp/insGC (c.802-8del17bp/insGC) or compound heterozygous IVS6-8del17bp/insGC and IVS8-2A_G (c1091-2A>G) mutations seemed to have a more severe disease phenotype based on electrophysiological testing. 10 Deletion at the exon 7 splice acceptor site causes an in-frame deletion of exon 7, resulting in the expression of a truncated protein.…”
Section: Genotype and Phenotype Correlation In Bcdmentioning
confidence: 99%
“…8,10 Electroretinography (ERG) examination typically shows decreased amplitudes of b-waves from both rods and cones 10 ; however, in one study that evaluated 15 BCD patients, more than 50% of patients had recordable standard ERG, and 2 had readings within normal limits 20 years after initial BCD diagnosis, suggesting that ERG may not always correlate with disease progression. 11 In one case report, standard ERG was normal, but multifocal ERG showed depressed central responses consistent with the macular lesion identified by OCT. 12 This suggests that the neuroretinal cells were still functioning in this patient despite RPE degeneration. Reports indicate that neuroretinal cell dysfunction in BCD patients is highly variable, and it is reasonable to suggest that the progression of RPE degeneration in BCD may originate from tissues on the basal side of the RPE rather than the neural cell layers.…”
mentioning
confidence: 90%
“…15 To date, over 50 mutations have been identified in BCD patients, with at least one mutation in each of the gene's 11 exons. [9][10][11][12][13][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Genotype analysis has shown that the most common pathologic CYP4V2 mutation is c.802-8_810del17insGC, which results in deletion of exon 7 in the mature transcript, though other mutations in each exon are also Copyright 2014 The Association for Research in Vision and Ophthalmology, Inc. www.iovs.org j ISSN: 1552-5783 linked to the disease. 16,17,28 Additionally, a relatively common polymorphism in CYP4V2 (rs13146272; Q259K), with a minor allele frequency of 45%, has been associated with deep vein thrombosis.…”
mentioning
confidence: 99%